-77=8x+3

Simple and best practice solution for -77=8x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -77=8x+3 equation:


Simplifying
-77 = 8x + 3

Reorder the terms:
-77 = 3 + 8x

Solving
-77 = 3 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-77 + -8x = 3 + 8x + -8x

Combine like terms: 8x + -8x = 0
-77 + -8x = 3 + 0
-77 + -8x = 3

Add '77' to each side of the equation.
-77 + 77 + -8x = 3 + 77

Combine like terms: -77 + 77 = 0
0 + -8x = 3 + 77
-8x = 3 + 77

Combine like terms: 3 + 77 = 80
-8x = 80

Divide each side by '-8'.
x = -10

Simplifying
x = -10

See similar equations:

| -126=-18r | | -11=x-6 | | w^2-6w-8=0 | | 7a+8=57 | | 4(3-x)-8=5-(3x-2) | | 4u^2-25u+25=0 | | 53+(-18)= | | 52+-50= | | 5.4c+6=0.6(9c+10) | | 3t+7=13 | | 5x-6x-5=72 | | -3+14= | | 4d-6=2(3d-4) | | x^2-14x+196=0 | | -25+25= | | 78=-5x+19 | | 18=-5x+19 | | 33=-5x+19 | | 27=-5x+19 | | 2c+6=0.5(4c+12) | | 6a+5b-2a+-b+7a+3c+a= | | 3(x)+5=8 | | 13=(y+2)-3 | | (x-14)=21 | | 9t-24=57 | | 6x=-4-1 | | 4t-25=9t | | v=.33bh | | w+2=16-6w | | x=120-2x | | x=120-2p | | 4x=3y-7x |

Equations solver categories